Theoretical Approaches to the Problem of Socialization of Future Teachers - Sivak, Nataliya (Pedagogical Discourse, 2015)
In the article the leading category values of socialization are selected in the different spheres of cognition; two groups of theoretical approaches to the students’ socialization of higher pedagogical educational establishment are revealed and analyzed: philosophical-methodological (philosophical, personality oriented, active, competitive) and specifically scientific (sociological, psychological and social pedagogical approaches). The process of socialization of students at higher educational establishment as a subject-objective influence and subject-subjecte co-operation of a teacher and a student in a pedagogical process is described.